A General Blockchain-Based Automatic Audit Scheme For Proofs Of Retrievability - Chen, Xiuyuan; Lin, Chao; Wu, Wei; He, Debiao (Computer journal, 2024)
Cloud storage has been widely used in remote data management, although correct storage of the outsourced file is still challenging in practice. Proofs of Retrievability (PoRs), a storage-oriented cryptographic tool, support integrity checking and efficient retrieval of the file. However, due to the lack of a fully credible oversight mechanism or a serious dependence on a trusted third party, most PoRs are incapable of achieving essential and straightforward trust between participants (i.e. the client and server). While blockchain shows promise in solving this trust issue, existing blockchain-based storage systems are scenario-constrained as they require private/permissioned or special-construct blockchains. Consequently, none of these systems provide robust and decentralized trustworthiness. We propose a general Blockchain-based Automatic Audit (BAA) scheme for PoR without limitations based on specific blockchain types. Specifically, we present BAA via stitching together a carefully designed or chosen array of sub-components such as storage proofs and Turing-complete smart contracts. We also integrate BAA with specific PoR models to prove its strong generality and availability. To our best knowledge, our proposal is the first blockchain-based approach that enhances traditional PoR models with both automatic audit and fair payment. The final analysis and implemented prototype on Ethereum demonstrate the utility of BAA.